PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL, TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU (KARYAWAN) DI KOTA MADIUN - Satrijo Budiwibowo (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Transactional leadership is described as providing an explanation of employees responsibilities and rewards they can expect if the specified standards is achieved. Transformational leadership approach motivates employees, so that they can thrive and achieve high levels of performance. In addition it is also necessary to support the performance of the good discipline of employees. Broadcasting companies who have employees working on the division of operational and management needed different leadership style to support the realization of optimal performance. This study used a qualitative approach. Sample was 136 people who are determined by purposive sampling technique. The research instrument used Likert scale models. Data analysis using validity test, realibitas test, the classical assumption, hypothesis testing, multiple linear regression analysis, analysis of correlation coefficients and determination. The results showed that together transactional leadership styles, transformational leadership styles, work discipline affect the performance of the company's employees broadcasting. Partially transactional and transformational leadership style had no effect on performance. And partially work discipline most dominant effect on performance. Keywords: Influence of Transactional, Leadership Style and Discipline Performance